Influence of contextual variables and the pressure to keep category on physical match performance in soccer players - Garcia-Unanue, J.; Pérez-Gómez, J.; Giménez, J.-V.; Felipe, J. L.; Gómez-Pomares, S.; Gallardo, L.; Sánchez-Sánchez, J. (PLOS ONE, 2018)
Previous studies have analysed the influence of contextual variables on performance and physical demands in soccer. However, the points needed to remain in the category have been an element that has not been analysed previously. The aim of the present study was to investigate the influence of match location, match period, strength of the opponent and the points required to keep category on physical performance in professional soccer players. Fourteen Spanish second B Division League matches played by a professional football team were analysed during the 2016/17 season using GPS devices. The 10 main players of each match used the GPS throughout the match. The variables of Total Distance (m), High Intensity Distance (m), High intensity Accelerations (n), Sprint Time (s) and Sprint Distance (m) were analysed. The most notable differences are found in Total Distance covered. Away games accumulated significantly more distance than those played at home, but only in the second half (+230.65 m, IC95%: 21.94 to 438.19, ES: 0.46, p = 0.031). There are no differences depending on the strength of the opponent. However, players covered greater distances during the first half in those matches that were played furthest from salvation (+235.86 m, 95% CI: 49.03 to 422.70, ES: 0.51, p = 0.014). Total Distance is the main parameter affected by situational variables. In addition, the pressure of being further away from saving the category increases the distance covered by players in a game.